2020
DOI: 10.1186/s12903-020-01341-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 pandemic on dental practice in Iran: a questionnaire-based report

Abstract: Background The highly contagious nature of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV2), besides the fact that dental procedures commonly generate blood and saliva droplets that could lead to the contagion have resulted in the closure of many dental clinics. In the present study, we aimed to evaluate the impact of coronavirus disease 2019 (COVID-19) pandemic on dental practice by conducting an online questionnaire among the Iranian dental practitioners and finding their perspectives on the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
80
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 31 publications
9
80
0
10
Order By: Relevance
“…This may be due to the idea that all patients have to be considered as potentially infectious. These concerns are consistent with the idea of multiple dentists performing no dental procedures except emergencies [ 31 ]. Corresponding to the number of confirmed COVID-19 cases in Hessen, we found higher levels of anxiety regarding self-infection and infection of others in all groups, but the highest levels were found among dental assistants, even though all HCP worked at the same place and time during the pandemic.…”
Section: Discussionsupporting
confidence: 84%
“…This may be due to the idea that all patients have to be considered as potentially infectious. These concerns are consistent with the idea of multiple dentists performing no dental procedures except emergencies [ 31 ]. Corresponding to the number of confirmed COVID-19 cases in Hessen, we found higher levels of anxiety regarding self-infection and infection of others in all groups, but the highest levels were found among dental assistants, even though all HCP worked at the same place and time during the pandemic.…”
Section: Discussionsupporting
confidence: 84%
“…For students, this meant new academic responsibilities mediated by remote and virtual strategies and some additional financial burdens in the context of great difficulties, among other circumstances [14,29]. In professionals, new labor adaptations were created, and this caused a decrease in working hours and even suspended face-to-face clinical activities [8][9][10]21]. Therefore, a decrease in income and an increase in domestic responsibilities were found [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…In general terms, dental practice has undergone numerous changes during the pandemic, specifically considering lockdowns and isolation measures. Studies conducted globally involving dental staff show that this situation has had a significant impact on their personal life, financial status, and the prospects of their professional career [9][10][11][12]. Similarly, other effects of the pandemic including the field of nutrition (a possible increase of overweight and obesity) [13], changes in family dynamics by the presence of children, or elders that represent some burden when they are economic providers, household income, among others [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When assessing the implementation of national and international COVID-19 guidelines for dental practice, we found that 97.83% of the surveyed dental offices implemented protective equipment for doctors [ 28 ] (PPE), 82.05% patient triage, 89.74% proper time gaps between patients, and 95.66% patient temperature checks. In line with international literature, this study also provides evidence for the effectiveness of PPE as an essential regulation for preventing the spread of the virus to and from healthcare providers and patients [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%